Heavy flavour physics: theory and experimental results in heavy quark physics and CP violation : proceedings of the Fifty-Fifth Scottish Universities Summer School in Physics, St. Andrews, 7 August - 23 August 2001 - Davies, C. (Institute of Physics Pub., 2011)
B-factories at SLAC and KEK started producing high quality results in 2001, while preparations for B physics at the LHC continue. Heavy Flavour Physics: Theory and Experimental Results in Heavy Quark Physics provides an introduction to and overview of recent developments in theory and experiments relevant to the physics of heavy flavors, particularly that of the b quark. The book reviews the field thoroughly from both experimental and theoretical perspectives. It includes important background material on the standard model, CP violation, lattice quantum chromodynamics, and Kaon decay experiments. Chapters are written by international experts and the whole book has been carefully edited to provide a coherent account of the field. The level is suitable for junior postdoctoral researchers and postgraduate students in particle physics.